The Impact of Software as a Service on Learning in Libyan Higher Education: An Empirical Study - Salha Aladad; Lamia Gweder; Abubaker Kashada; Awatif Ali Snon; Khalid Jumma Bisher (Surman Journal of Science and Technology, 2025)
Cloud computing has emerged as a significant paradigm in the information technology industry, encompassing three primary service models: Infrastructure as a Service (IaaS), Platform as a Service (PaaS), and Software as a Service (SaaS). This study focuses on the SaaS model and its implementation in educational contexts, which necessitates acceptance from all educational stakeholders. Classified as a case study, the research evaluates the impact of Software as a Service (SaaS) on academic performance in the Computer Department at Surman College of Science and Technology by comparing academic averages before and after the implementation of cloud-based applications. The study employs one questionnaire which target 153 students collecting feedback over multiple academic semesters and comparing it with conventional pedagogical approaches, using SPSS in order to analysis data. This methodology aims to elucidate the requisites for efficacious SaaS implementation and delineate its advantages.